PI‐RADSv2: How we do it. Issue 1 (25th February 2017) - Greer, Matthew D.; Choyke, Peter L.; Turkbey, Baris
Abstract : Much criticism has been leveled at screening for prostate cancer using prostate‐specific antigen (PSA) testing, yet there is no suitable replacement to improve the detection of clinically significant cancer (CSC). Prostate multiparametric magnetic resonance imaging (mpMRI) combined with mpMRI‐guided biopsies is one possible solution, as it reduces detection of low‐grade disease and increases detection of CSC. However, mpMRI is critically limited by lack of standardization across institutions and low interobserver agreement. The Prostate Imaging Reporting and Diagnostic System version 2 (PI‐RADSv2) aims to address these concerns. We discuss the clinical and technical considerations for implementing PI‐RADSv2, how we have adapted to PI‐RADSv2, and review current research. While PI‐RADSv2 represents a major step forward for standardizing prostate mpMRI, it does not provide a level of standardization that is routine with clinical blood tests and reader reproducibility remains an issue. Future research should seek to further improve quality assurance of mpMRI building on the important contributions of PI‐RADSv2. Level of Evidence : 5 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:11–23